THE APPLICABILITY OF EXISTING COMPUTER TECHNOLOGY TO AUTOMATE FUZZY SYNTHESIS OF TRAFFIC LIGHT UAV IN ADVERSE WEATHER CONDITIONS - L. N. Lysenko; N. T. Sham (Научный вестник МГТУ ГА)
The results of the analysis of the applicability of known application software systems for automated synthesis of fuzzy control traffic light UAV during its flight in adverse weather conditions. The solution is based on a previously formulated and put into consideration the principle of permissible limited a priori estimation of the uncertainty of aerodynamic characteristics of UAVs.